Linguistic Review on Journalistic Language in the News Heading on Indonesiaalyoum.com during January-June 2024 - Dian Malinda; Akhmad Fadhillah Kartono; Haniah; Aswan (Research Synergy Foundation, 2025)
Indonesiaalyoum.com is the first Indonesian news portal to provide news in Arabic, offering comprehensive information about Indonesia to the Arab and Islamic nations. However, there is no previous study on journalistic language on this website. This research is providing significant academic and practical contributions to Islamic studies. Academically, it deepens the knowledge of Arabic journalistic practices in Indonesia, discloses how Islamic and national issues are represented. Practically, it entails a roadmap for Muslim communicators to productize ethical and effective headlines, translate news, offer editorial advice, and foster media literacy among Muslim readers. The study represents a notable advancement in Islamic social science as it addresses an issue of cross-cultural communication and media ethics through the lens of linguistic analysis of Arabic-language news headlines within the wider frameworks of intercultural communication and media ethics in Islamic contexts. Working in the area where Arab and Indonesian Muslim cultures meet, Indonesiaalyoum.com is not only a source of information but also a means of cross-cultural engagement in the global Muslim society. The method utilized in this study is descriptive research with an error analysis technique using semantic and syntactic analysis. The process began with collecting data, which consisted of 25 articles from January to June 2024, making notes, and then analysing it using semantical and syntactical approaches. The results of the research can be concluded that the articles on Indonesia.com are based on two main sources: journalist correspondence and translations of other publications. The translated news source is particularly mentioned at the end of the articles, which are published until February 15, 2024. Afterwards, some subsequent publications implied it tacitly. This study also identified errors in the use of journalistic language, including spelling errors, mistranslations, and misinformation. In addition, the most common translation technique employed in these articles is the literal translation.